Morphological evaluation of self-affine thermally grown KBr thin films. (4th December 2019) - Rai, R; Yadav, R P; Pandit, Triloki; Jammal, Nabeel; Singh, A K; Singh, B K
Abstract: In this article, a fractal concept is used to evaluate the morphological features of KBr layers, deposited in a controlled vacuum environment. To the best of our knowledge, for the first time, self-affine or self similar nature of KBr film surfaces was examined by autocorrelation function. Theoretical estimations revealed that irregularity/complexity of growing KBr layers was significantly influenced by the thickness. The global interface width and lateral correlation length were monotonically decreased with increasing film thickness. On the contrary, fractal dimension and local roughness exponent, estimated by height-height correlation function, did not suggest such dependency.